1987
DOI: 10.1007/bf00690895
|View full text |Cite
|
Sign up to set email alerts
|

Effects on physical performance of intrinsic sympathomimetic activity (ISA) during selective ?1-blockade

Abstract: In 15 healthy, not specifically trained volunteers (age: 26.6 +/- 2.7 years) single equipotent doses of a selective beta 1-blocker with intrinsic sympathomimetic activity (ISA) (200 mg Epanolol-Visacor; V) and of a selective beta 1-blocker without ISA (100 mg Metoprolol; M) were compared with placebo (P) with respect to their influence upon physical performance capacity and metabolism in a random, double blind, cross-over experimental setting. The subjects underwent three step by step incremental treadmill tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
3
10
0
2
Order By: Relevance
“…2) but this difference did not reach statistical significance. Kullmer et al (1987) have found significantly higher LA values, while others have found unchanged (Gullestad et al 1989;Hambrecht et al 1995;Hugson and Smyth 1983;Reybrouck et al 1977;Vanhees et al 2000;Wittke and Kemmler 1999) or decreased LA concentrations (Schnabel et al 1983) during submaximal or maximal exercise tests. A possible explanation for these contrasting findings could be intra-individual differences in LA concentrations that may have been influenced by differences in glycogen stores, nutritional status or daily variation in physiological performance capacity (Aunola and Rusko 1992;Hofmann et al 1994a;Yoshida 1984).…”
Section: At and Mlss Testmentioning
confidence: 92%
See 2 more Smart Citations
“…2) but this difference did not reach statistical significance. Kullmer et al (1987) have found significantly higher LA values, while others have found unchanged (Gullestad et al 1989;Hambrecht et al 1995;Hugson and Smyth 1983;Reybrouck et al 1977;Vanhees et al 2000;Wittke and Kemmler 1999) or decreased LA concentrations (Schnabel et al 1983) during submaximal or maximal exercise tests. A possible explanation for these contrasting findings could be intra-individual differences in LA concentrations that may have been influenced by differences in glycogen stores, nutritional status or daily variation in physiological performance capacity (Aunola and Rusko 1992;Hofmann et al 1994a;Yoshida 1984).…”
Section: At and Mlss Testmentioning
confidence: 92%
“…Using b 1 -selective blockade, previous studies have shown both a reduction in maximal aerobic performance (Kullmer et al 1987;Schnabel et al 1983) as well as no change (Brion et al 2000;Gullestad et al 1989;Hughson and Smyth 1983;McLeod et al 1984;Sklar et al 1982;Wittke and Kemmler 1999) in healthy subjects and in patients having coronary artery disease or arterial hypertension. In agreement with Brion et al (2000), we found no differences in maximal power output (Table 3).…”
Section: Maximal Valuesmentioning
confidence: 98%
See 1 more Smart Citation
“…unterschiedliche Abbruchkriterien beeinflusst. Die Lage der Lactatleistungskurve wird dagegen bei normalen Untersuchungs-und Ernährungsbedingun-gen sowie durch Calciumantagonisten oder Betarezeptorenblocker nicht beeinflusst [21,23]. Auch bei Patienten mit einer unterhalb der anaeroben Schwelle liegenden kardialen Belastbarkeitsgrenze lässt sich die submaximale Leistungsfähigkeit durch adäquate Übungsmaßnahmen verbessern und auf diesem Wege dokumentieren.…”
Section: Dokumentation Des Therapieerfolgsunclassified
“…Bis zum Ausschluss potentiell gefährlicher Arrhythmien sind intensive körperliche Belastungen zu vermeiden. Bei der medikamentösen antiarrhythmischen Therapie gelten die in den jeweiligen Leitlinien festgelegten Grundsätze [8,17]; es sind jedoch die mit der jeweiligen Sportart verbundenen körperlichen und mentalen Belastungsmomente in der Beurteilung des Therapieerfolges zu berücksichtigen [19,20]. Zusätzlich muss berücksichtigt werden, dass unter den antiarrhythmischen Präparaten -Rezeptoren-Blocker in bestimmten Sportarten aufgrund der Dopingbestimmungen nicht zulässig sind.…”
Section: Introductionunclassified